Existence and Uniqueness Solution of Second Order Nonlinear Integro-Differential Equations with Boundary Conditions - Ghada Jameel (College of Education for Pure Sciences, 2008)
ABSTRACT In this paper we study the existence and uniqueness solution of second order nonlinear integro-differential equations with boundary conditions, by using the Picard approximation method which is given by . Where we extend some results gained by .